Cure in metastatic breast cancer - Westphal, Theresa (Memo, 2018)
Oligometastatic disease characterizes a distinct subgroup of metastatic breast cancer patients that might benefit from different treatment strategies to achieve long-lasting remission and potentially cure. Those long-lasting remissions are reported after locoregional treatment of the primary tumor and all metastatic sites in several case series; however, unlike other tumor entities, prospective data are lacking. Furthermore, tumor eradication by excellent systemic anticancer therapy with novel chemotherapies and targeted agents can lead to long-term survival. In addition, reactivation of the host immune defense by immuno-oncologic drugs can achieve long-lasting tumor control. So far, unfortunately, checkpoint inhibitors as monotherapy have led to responses only in a small percentage of patients with metastatic breast cancer. This short review summarizes available data on long-lasting remissions and potential cure in metastatic breast cancers. It describes and discusses data on locoregional treatment, chemo-, antibody- and immunotherapy and tries to select individual patients for whom a multidisciplinary treatment approach with curative intention might be an option to achieve long-term survival.